Enhanced Impact of Cholesterol Absorption Marker on New Atherosclerotic Lesion Progression After Coronary Intervention During Statin Therapy - Mori, Kenta (J Atheroscler Thromb, 2017)
Aim: Clinical trials suggest that residual risks remain for coronary artery disease (CAD) during low-density lipoprotein cholesterol (LDL-C) lowering therapy. We aimed to investigate the role of exogenous lipids in the prognosis of CAD after percutaneous coronary intervention (PCI). Methods: A total of 145 patients with CAD, who underwent elective PCI, and 82 non-CAD (control) patients were enrolled in this study. CAD patients underwent follow-up coronary angiography 6–9 months after PCI, and were classified into three groups: 1) patients who showed in-stent restenosis (ISR) in the original stented segment, 2) patients with other non-target coronary atherosclerotic lesions (de novo), and 3) patients with neither ISR nor a de novo lesion. Biochemical analyses were performed on fasting serum samples at the time of follow-up coronary angiography. Results: Despite the controlled serum LDL-C levels, CAD patients with statin showed elevated cholesterol absorption marker campesterol/total cholesterol (TC), synthesis marker lathosterol/TC, campesterol/lathosterol ratio, and apolipoprotein B48 (apoB48) concentration compared with non-CAD patients. The high campesterol/TC, campesterol/lathosterol ratio, and apoB48 concentration were associated with de novo lesion progression after PCI. In stepwise multivariate logistic regression analysis, campesterol/TC and apoB48 concentrations were independent risk factors for de novo lesion progression in statin-treated CAD patients after PCI. Conclusion: The increase of cholesterol absorption marker and apoB48 concentration may lead to the progression of de novo lesions, and these markers may represent a residual risk during statin treatment after PCI.